2020
DOI: 10.3390/pr8030330
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Compounds of Branches from P. halepensis Oily Liquid Extract and S. terebinthifolius Essential Oil and Their Potential Antifungal Activity

Abstract: In the present study, the antifungal activity of wood treated with Pinus halepensis branch n-hexane oily liquid extract (OLE) and Schinus terebinthifolius branch essential oil (EO) was evaluated against the growth of four phytopathogenic fungi—Bipolaris oryzae, Fusarium oxysporum, Fusarium solani, and Rhizoctonia solani. Air-dried wood samples of Pinus roxburghii were autoclaved, and each wood received 100 µL of the concentrated oils from P. halepensis and S. terebinthifolius. The main compounds identified in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 82 publications
(115 reference statements)
2
35
0
Order By: Relevance
“…Thus, these aldehydes might be good compounds for playing a reserving role against human diseases caused by bacteria or as food preservatives, or might be a good alternative to other highly toxic disinfectants for hospital equipment. Recently, Pinus halepensis branch HeOE showed the presence of 2-undecenal, (Z)-2-decenal, nonanal, (2E)-2-decenal, and decadienal as main compounds, with a good antifungal activity against B. oryzae and F. oxysporum [89].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these aldehydes might be good compounds for playing a reserving role against human diseases caused by bacteria or as food preservatives, or might be a good alternative to other highly toxic disinfectants for hospital equipment. Recently, Pinus halepensis branch HeOE showed the presence of 2-undecenal, (Z)-2-decenal, nonanal, (2E)-2-decenal, and decadienal as main compounds, with a good antifungal activity against B. oryzae and F. oxysporum [89].…”
Section: Discussionmentioning
confidence: 99%
“…To control fungal growth, biosynthesis of mycotoxin, and food contamination, three main approaches (physical, biological, and chemical treatments) were recognized and used against mycotoxigenic fungi [7,23,[38][39][40][41][42][43][44][45]. The crude EO was more effective than the major compounds, for example, the EO extracted from some Eucalyptus species such as C. camaldulensis was more active against Pseudomonas aeruginosa than the major constituents such as α-pinene, 1,8-cineole, and p-cymene [46].…”
Section: Introductionmentioning
confidence: 99%
“…Table 7 shows that the minimum inhibitory concentrations calculated for the essential oil treatments ranged between 250 and 400 mg/L, which were lower than those from Mancozeb as a chemically positive control of all fungal isolates (range from 20 to 40 mg/L). Previous work showed that oil extracted with n-hexane at a concentration of 3% from Pinus halepensis showed an FMGI value of 80% against the growth of B. oryzae, while the EO from Schinus terebinthifolius observed the values of 74.44% and 71.66% at 3% and 2%, respectively [35]. Moreover, Cymbopogon martinii, O. vulgare and Cinnamomum zeylanicum EOs showed significant antifungal activities against F. graminearum and F. culmorum in wheat grains with FMGI percentages of 90.99% and 68.13%, respectively [61].…”
Section: Molecular Identification Through the Internal Transcribed Spmentioning
confidence: 99%
“…GC/MS with Xcalibur 3.0 data system has threshold values to confirm that all the MS of the compounds were attached to the library. Therefore, measuring their standard index (SI) and reverse standard index (RSI), values ≥ 650 are acceptable to confirm the compounds [35,[75][76][77][78].…”
Section: Gc/ms Analysis Of the Essential Oilsmentioning
confidence: 99%
See 1 more Smart Citation